A quasi coherent spread spectrum decoder for satellite communications using a low rate convolutional code - Tomlinson, M.; Abu Rgheff, M.A. (1996 IEEE 4th International Symposium on Spread Spectrum Techniques and Applications : technical program, proceedings, September 22-25, 1996, Electoral Palace, Mainz, Germany, 1996)
A new form of bandpass convolutional decoder is presented. The decoder has as its basis, the classic Viterbi algorithm, but uses envelope (energy) detection in order to cope with a frequency offset, phase rotating received signal. The advantage of this decoder is that it does not need to be proceeded by a modem and is not subject to the problems of cycle slips. It can operate at negative input SNR values and is well suited to the decoding of low rate convolutional codes as may be used in CDMA systems. An example is given of a 1/6 rate system operating at 16 kbits/sec using a EUTELSAT satellite.